Răspuns :
P=2(L+l)=106
L=3l+5
2(3l+5+l)=106
2(4l+5)=106
4l+5=53
4l=53-5
4l=48
l=12
L=3*12+5=41
l=Ppatrat
Ppatrat=4lp, lp=latura patratului
4lp=12
lp=3
L=3l+5
2(3l+5+l)=106
2(4l+5)=106
4l+5=53
4l=53-5
4l=48
l=12
L=3*12+5=41
l=Ppatrat
Ppatrat=4lp, lp=latura patratului
4lp=12
lp=3
L-5=3l
L=3l+5
P=2l+2L
P=106 inlocuim lungimea in formula perimetrului cu 3l+5
2l+2(3l+5)=106
2l+6l+10=106
8l+10=106
8l=106-10
8l=96
l=12
L=3*12+5=36+5=41
l=Ppatrat
12=Ppatrat
Ppatrat=4l
4l=12
l=12:4
l=3
L=3l+5
P=2l+2L
P=106 inlocuim lungimea in formula perimetrului cu 3l+5
2l+2(3l+5)=106
2l+6l+10=106
8l+10=106
8l=106-10
8l=96
l=12
L=3*12+5=36+5=41
l=Ppatrat
12=Ppatrat
Ppatrat=4l
4l=12
l=12:4
l=3